Answers

2015-06-04T21:46:55+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
This is a special product which is the difference of two squares:
(a+b)(a-b) = a² - b²
(8-3x)(8+3x) = 64 - 9x²
0
2015-06-04T21:47:16+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
As you can see, this expression is related in the form:
        
            (x-y) (x+y) 
The rule states that if an expression is in the form

(x-y) (x+y) 
its answer is:  x² - y²

Solve:
                    (8 - 3x) (8 + 3x) = 64 - 9x²
Check:
              F = 8²
              O = 8 (3x)
              I = 8 (-3x)
              L = (-3x) (3x)
            = 64 + 24x - 24x - 9x²
            = 64 - 9x², Correct

0